2014
DOI: 10.5588/ijtld.12.0980
|View full text |Cite
|
Sign up to set email alerts
|

Use of biomass fuel in households is not a risk factor for pulmonary tuberculosis in South Ethiopia

Abstract: We found no evidence of an association between the use of biomass fuel and TB. Low statistical power due to the selection of neighbourhood controls might have contributed to this negative finding. We would advise that future protocols should not use neighbourhood controls and that they should include measurements of indoor air pollution and of exposure duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…A recent systematic review and previous reports have shown that history of TB contact was associated with a high risk of TB [30, 46–48]. Findings by the current study are in line with those of a systematic review and large epidemiological surveys that have established the association between history of TB contact and higher risk of TB [47, 49, 50].…”
Section: Discussionsupporting
confidence: 91%
“…A recent systematic review and previous reports have shown that history of TB contact was associated with a high risk of TB [30, 46–48]. Findings by the current study are in line with those of a systematic review and large epidemiological surveys that have established the association between history of TB contact and higher risk of TB [47, 49, 50].…”
Section: Discussionsupporting
confidence: 91%
“…One limitation of this study was selection of tuberculosis cases from a regional tuberculosis centre, whereas controls were recruited from a nearby hospital. By contrast, Lakshmi and colleagues42 reported no association between tuberculosis and kerosene stove use in a study in India, and Woldesemayat and colleagues43 also showed no association between tuberculosis and kerosene lamp use in Ethiopia. In summary, the relationship between HAP and tuberculosis in adults is not established.…”
Section: Respiratory Infectionsmentioning
confidence: 93%
“…They reported a summary OR for all participants of 1·30 (95% CI 1·04–1·62) and 1·70 for women (1·10–8·20), although there was heterogeneity among study results. A study by Woldesemayat and colleagues,43 published after the meta-analysis, showed no association between tuberculosis and use of solid fuels for cooking, but nearly all participants used solid fuels, so there was insufficient exposure variation for useful analysis 43…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…Taken in Nepal and India that investigated the relationship between tuberculosis (TB) and indoor biomass, evidence was provided that linked exposure to smoke from kerosene fuel combustion, either in stoves or in lamps to TB [46,47]. Interestingly, similar studies conducted recently in Southern Ethiopia found no evidence of an association between the use of biomass fuel and TB [48]. The authors cited low statistical power due to the selection of neighbourhood controls as a likely contributor to these negative findings.…”
Section: Pulmonary System Effectsmentioning
confidence: 93%